Identifying topology in power networks in the absence of breaker status sensor signals - Oliveira, Rui; Bessa, Ricardo; Iranda, Vladimiro M (IEEE Mediterranean Electrotechnical Conference, 2018)
This paper presents the concept of a tapered deep neural network, subject to unsupervised training layer by layer, under a criterion of maximum entropy, to perform the estimation of breaker status in the absence of a specific sensor signal. The almost perfect prediction power of the model confirms the conjecture that the knowledge of the topology of a network is hidden in the electric measurement values in the network. A test case is presented with computing speed accelerated by using a GPU (graphics processing unit). The comparison with a previous model illustrates the superiority of the novel approach.